Integrated assessment of land use/land cover changes and hydrological impacts in the nile river basin: a case study of Rwanda hydro-unity network - Hakorimana, Egide; Xi, Chen; Kurban, Alishir; Nsanzabaganwa, Justin; Umuhoza, Jeanine; Niyonsenga, Schadrack; Umugwaneza, Adeline; Habimana, Chantal (Frontiers in Environmental Science, 2025)
This study evaluates the impacts of land use and land cover (LULC) changes on streamflow dynamics and water availability within the Rwanda Hydro-Unity Network catchment, part of the Nile River basin. Utilizing the Soil and Water Assessment Tool (SWAT) and the Climatic Water Balance (CWB) model, we analyze hydrological changes from 1991 to 2020. The findings reveal a significant increase in surface runoff, water yield, and evapotranspiration, mainly driven by urban expansion and agricultural intensification, while groundwater recharge and percolation have declined. Climate variability has also contributed to increased evapotranspiration and seasonal water deficits, exacerbating drought risks. The key Findings showed that (1) LULC Changes (1991–2020): Cropland increased from 33.2% to 72.0%, Built-up areas expanded from 0.9% to 2.7% and Forest cover declined sharply from 49.9% to 11.8%. (2) Hydrological Changes: Surface runoff increased from 144.99 mm to 201.73 mm, Total water yield rose from 304.83 mm to 338.25 mm, Groundwater recharge declined from 105.58 mm to 88.27 mm and Evapotranspiration increased from 600.39 mm to 657.32 mm. (3) Climate Variability and Water Balance: Rising temperatures increased potential evapotranspiration (PET), reducing available water and the long dry season (June–September) showed the most significant decline in water balance. (4) Flood Risks and Adaptation Strategies: Urbanization has increased flood risks due to expanded impervious surfaces, Sustainable solutions, such as reforestation, improved urban drainage, and wetland restoration, are necessary. The study emphasizes the need for integrated land and water management strategies, including sustainable land-use policies, climate adaptation measures, and enhanced flood mitigation practices to ensure long-term water security in Rwanda.